Desenvolvimento de estratégias de leitura para distinção entre fato e opinião - Nogueira, Carla Rafaela Rodrigues (2024)
This research aims to discuss how the reading comprehension of 9th grade students at a municipal public school in Fortaleza can favor their ability to distinguish between fact and opinion. From this, we highlight aspects covered such as reading strategies, argumentative markers and argumentation, distinction between fact and opinion and the role of modalizers in textual genres that help differentiate between fact and opinion. According to data from the Organization for Economic Co-operation and Development (OECD, 2021) report, entitled “Readers of the 21st century: developing literacy skills in a digital world”, published in February 2021, and counting on a survey of information on 70 countries, including Brazil, 67% of 15-year- old students in our country cannot identify the difference between fact and opinion. In order to achieve the objectives of this work, we developed a bibliographic research to support an intervention proposal. To succeed in our purpose, we resort to theoretical foundations in Solé (1998), Alves (2010), Nocrato (2016), Kleiman (2002), Koch (2002), Borges (2015), Bakhtin (2000) and Marcuschi (2005). As a result, in establishing the relationship between the questions of the chain of activities and the theoretical conceptions, we found that the aforementioned authors point out that reading is the central object of learning, that reading strategies are individual subjective constructs, although there are general parameters established regarding the distinction between fact and opinion, that is, that it is a task that requires the use of cognitive, grammatical and argumentative resources, considering the role of. In this research, this result points to the direct presentation of a certain event, whose criterion is the possibility of verification without any variation in findings, while opinion is the expression of the sender's thoughts, therefore, subjective, and subject to different understandings, whose guideline It is individuality in the formation of value judgments and in historical social experiences. Given this, we conclude, in view of the central focus of this research, that, in the context of teaching, it is necessary to consider the subjectivity of students for the analytical process of results in the development of communicative skills. In the process of preparing the intervention proposal through activities to develop reading comprehension, we also verified that it is pertinent that the theoretical foundations support the teaching practice in the search for ways to improve reading strategies for the understanding of the distinction between fact and opinion and the argumentative construction, pertinent to periodic school or large-scale evaluative events.